"Devi Mangiare!" [You have to eat!]: Experiences of disordered eating among Italian-Australian women. Issue 1 (4th March 2022) - Caruso, Michelle; Moulding, Nicole
Abstract: In this article, the researchers report findings on how food meanings, culture and gender intersect in the experiences of Italian-Australian women. In-depth narrative interviews were thematically analyzed using a feminist social constructionist framework informed by anthropological theories about "foodways" and culture. Three core themes were identified in the women's narratives: " il cibo e' tutto, il cibo e amore " – "food is everything, food is love"; " fare la bella figura " – "to make a good impression"; and " il mio piatto " – "it's my plate". The researchers demonstrate how gendered expectations of women in Italian-Australian culture intersect with food meanings, cultural ideals and practices to produce distinct experiences of disordered eating and restricted access to formal support. The relevance of the findings are likely to be applicable to other migrant communities across the world. Particularly where ethnic communities retain distinctive food related meanings and practices post migration, that may intersect with cultural ideals venerating female thinness and the psycho-medical models and practices that pathologize disordered eating.